Pott Puffy Tumor : Case Report - Ade Wirdayanto; Hadiyan Adhli Muhammad (Fakultas Kedokteran Universitas Riau, 2023)
Pott puffy tumor (PPT) is an abscess of the subperiosteal os, frontalis. Frontalis subperiosteal abscess is often found in cranial osteomyelitis. Cranial osteomyelitis is an inflammatory process of the cranial bones, mainly caused by pyogenic organisms. The most common cause of cranial osteomyelitis in developing countries is paranasal sinusitis. One of the causes of PPT is an infection of the frontal sinus. Intracranial complications are the most common complications of PPT, one of which is a cerebral abscess in the frontal lobe. In this case report, the patient complained of forehead swelling that spread to both upper eyelids. There is a history of boils on the left side of the forehead since 3 weeks ago but was not treated medically. On physical examination, there was no neurological deficit. In the initial action, aspiration of the swelling results in the form of pus. Based on the results of a plain head CT scan and 3D skull bones, the results obtained were an appearance of an abscess in the subperiosteal frontal bone and osteomyelitis of the frontal bone. The patient underwent debridement craniectomy and further therapy in the form of intravenous antibiotics. As a follow-up examination, an examination of pus culture and examination of anatomical pathology were carried out, and obtained cranial osteomyelitis results but found no pathogenic germs.